PERLINDUNGAN HUKUM TERHADAP ANAK DALAM KELUARGA POLIGAMI - Muhamad Jauhari (Turatsuna : Jurnal Keislaman dan Pendidikan, 2019)
The rights of polygamous family children in positive law are: a) civil rights; b) the right to protection; c) the right to education and maintenance; d) children's rights to get welfare; e) children's rights to be taken care of their legal affairs. Positive law and Islamic law perspectives on violations the rights of polygamous children, namely for parents who violate the rights of polygamous family children, can be revoked as their parents' guardianship. In the Islamic law perspective against violations the rights of polygamous children are subject to moral sanctions and legal sanctions. This legal sanction is a form of world punishment for perpetrators of child rights violations. Keywords: legal protection, children's rights, polygam Hak-hak anak keluarga poligami dalam hukum positif yaitu: a) hak keperdataan; b) hak mendapat perlindungan; c) hak atas pendidikan dan pemeliharaan; d) hak anak untuk mendapat kesejahteraan; e) hak anak untuk diurus urusan hukumnya. Perspektif hukum positif dan hukum Islam terhadap pelanggaran atas hak anak poligami yaitu bagi orang tua yang melanggar hak anak keluarga poligami dapat dicabut kuasa asuhnya sebagai orang tua terhadap anaknya. Dalam perspektif hukum Islam terhadap terhadap pelanggaran atas hak anak poligami dikenakan sanksi moral dan sanksi hukum. Sanksi hukum ini sebagai bentuk hukuman dunia terhadap pelaku pelanggaran hak-hak anak. Kata Kunci: perlindungan hukum, hak anak, poligami